Removal of multiple heavy metals from mining-impacted water by biochar-filled constructed wetlands: Adsorption and biotic removal routes. (July 2021) - Chen, Jinquan; Deng, Shengjiong; Jia, Wei; Li, Xuan; Chang, Junjun
Graphical abstract: Highlights: Granular biochar was filled in CWs to treat acidic mining-impacted water (MIW). Biochar CWs had better abiotic Cu/Zn/Cd removal and macrophyte growth and high pH. Liquid organic waste (LOW) addition drove biogenic routes in CWs for MIW treatment. Metals were predominantly deposited in CW media, with marginal uptake by macrophytes. Functional microbial groups were stimulated by LOW for efficient MIW biotreatment. Abstract: Granular biochar made from walnut shells was layered into sand-based constructed wetlands (CWs) to treat simulated mining-impacted water (MIW). The results showed that the biochar media exhibited markedly high capacities for metal binding and acidity neutralization, supported notably better plant growth and mitigated metal transfer from the plant roots to the shoots. The addition of organic liquid wastes (domestic sewage and plant straw hydrolysation broth) stimulated biogenic sulfate reduction after 40 d of adaptation to effectively remove multiple heavy metals in the MIW. The microbial community compositions were prominently regulated by organic carbon, with desirable communities dominated by Cellulomonas and Desulfobulbus formed in the CWs for MIW biotreatment. The role of macrophytes in the CWs in MIW treatment was insignificant and was dependent on operation conditions and metal species. A biochar-packed CW system with liquid organic waste supplementation was effective in metal removal and acidity neutralization of MIW.